The age effect on the association between the scavenger receptor class B type I (SR-BI) polymorphism and HDL-C level: Tehran Lipid and Glucose Study. (August 2014) - Faam, Bita; Daneshpour, Maryam Sadat; Hedayati, Mehdi; Halalkhor, Sohrab; Mansournia, Mohammad Ali; Zarkesh, Maryam; Azizi, Fereidoun
Abstract Introduction: The scavenger receptor class B type I (SR-BI) is a key component in the reverse cholesterol transportation. The aim of this study was to assess the association between exon1 (G → A) polymorphism of SR-BI gene and lipid profiles among the Tehran Lipid and Glucose Study (TLGS) population. Materials and methods: This cross-sectional study included 774 adults (322 males and 452 females) aged 20–70 years who were randomly selected from among TLGS population. Anthropometrical and biochemical variables for participants were measured. Selected SR-BI gene polymorphism was determined with restriction fragment length polymorphism, via Alu restriction enzyme. Results: Minor allele frequency for SR-BI polymorphism in the selected population was 0.159. Allele frequencies were in conformity with Hardy–Weinberg equilibrium. Association between (G → A) SR-BI polymorphism and high density lipoprotein cholesterol (HDL-C) and HDL3 was significant only after adjustment for age as a potential covariate (p = 0.046, 0.041, respectively); however, the results did not improve after adjustment for sex. Discussion: The result of this study confirms the role of age as a potential confounder which could modify the association between the SR-BI single nucleotide polymorphism and HDL-C level.